Comparative Analysis of Seaweed Cultivation Business Income Before and After Getting KUR Financing in Liya Togo Village, Wakatobi Regency - La Ode Achmad Najhan; Ine Fausayana; Yusna Indarsyih (International Journal of Technology and Education Research, 2025)
This research aims to (1) determine the amount of seaweed cultivation business income in Liya Togo Village, South Wangi-Wangi District, Wakatobi Regency, (2) analyze the comparison of seaweed cultivation business income before and after obtaining people's business credit (KUR) financing in Liya Village Togo, South Wangi-Wangi District, Wakatobi Regency. The population in the research were all seaweed cultivation business actors in Liya Togo Village, precisely in South Wangi-Wangi District, Wakatobi Regency, who had received 29 people's business credit (KUR) funding. Sampling from the population was carried out using a non-probability sampling method, namely the saturated sampling method (census). So the total population and sample size are 29 people. Research analysis uses income analysis and paired t-test analysis. The results of this research show that there are differences in seaweed farming income in Liya Togo Village before and after the existence of People's Business Credit (KUR). Seaweed farming income is higher after the People's Business Credit (KUR) program. The difference in seaweed farmers' income is due to differences in costs and farmers' income after getting People's Business Credit (KUR). After getting People's Business Credit, the income of seaweed farmers, the capital they get increases